Diphtheria, tetanus and poliovirus antibody persistence 5 years after vaccination of pre-schoolers with two different diphtheria, tetanus and inactivated poliomyelitis vaccines (Td-IPV or DT-IPV) and immune responses to a booster dose of DTaP-IPV. Issue 32 (31st July 2015) - Gajdos, Vincent; Vidor, Emmanuel; Richard, Patrick; Tran, Clément; Sadorge, Christine
Abstract Introduction This follow-up study assessed the 5-year persistence of vaccine-induced antibodies (Td-IPV or DT-IPV) and the immune response to a booster dose of DTaP-IPV. Methods This was an open-label, parallel-group (two arms), multicentre trial performed at 44 study sites in France. Children aged 11–13 years, of either sex, who received Td-IPV (Revaxis®) and DT-IPV (DT Polio®) vaccines at 6 years of age in one previous open-label trial with no further vaccination against diphtheria, tetanus, pertussis or poliomyelitis, were enrolled. All participants received a single intramuscular booster dose (0.5 mL) of DTaP-IPV vaccine (Tetravac-Acellulaire®). Study endpoints were based on antibody persistence and post-booster immune responses. Safety was monitored throughout the study. Descriptive statistics were used for all analyses. Results Of the 758 children included in the previous study, 274 were included in this follow-up study; 129 had previously been vaccinated with Td-IPV, and 145 had previously received DT-IPV. At least 96.5% of participants in both groups presented an anti-diphtheria and anti-tetanus concentration ≥0.01 IU/mL, and anti-poliovirus types 1–3 titres ≥ 8 (1/dilution). Following vaccination with DTaP-IPV, anti-diphtheria and anti-tetanus antibody concentrations ≥0.1 IU/mL and anti-poliovirus types 1–3 antibody titres ≥8 (1/dilution) were achieved in all participants. DTaP-IPV was well tolerated in this study. There were no serious adverse events during the study, and no participant withdrew because of adverse events. Discussion The present study confirmed the long-term immunity conferred by Td-IPV when given as a booster dose, and supports the use of Td-IPV as a second booster at 6 years of age in children previously vaccinated against diphtheria, tetanus and poliomyelitis types 1–3.